STUDY OF THE BASKETBALL AND VOLLEYBALL THEMATIC UNIT BASED ON THE STUDENTS’ PERFORMANCE - Zsuzsa NAGY; Anetta MÜLLER; Melinda BÍRÓ; Eszter BODA; Iuliana BOROS-BALINT (Studia Universitatis Babeş-Bolyai: Educatio Artis Gymnasticae, 2017)
The aim of our research is to assess the students’ performance within the teaching units can be found in the syllabus. The benefit of the new method modeled by us is to give a detailed and comprehensive picture about the students’ load ability, endurance (individually), as well as make the students’ evaluation easier. At the same time it facilitates to confirm the efficiency of the educational system and the teacher’s successfulness. In Physical Education, we are demonstrating a new method in our research to make differentiation. The students’ lesson activity can determine the conditions how to form the certain groups. No students are those that adapt the tasks unified by everybody but after the group formation (based on measuring), the students perform the tasks correlated to the group abilities. Therefore, the load ability will be unified for everybody according to their capacity by doing the various exercises. The research showed the efficacy of the method as well as we can get an accurate picture about the same loading rate of the students’ performance who can be loaded or less loaded by comparing two teaching units after performing the exercises controlled by measuring. The WHO (2010) offer a medium and high intensity physical activity for the individuals aged at 5-17 in minimum 60 minutes. The objective is to develop the skeletal, joint and musculoskeletal system as well as the cardiorespiratory endurance with aerobic exercises. This measuring method helps to test whether the medium or high intensity load, prescribed by the WHO, can be accomplished or cannot, measuring the effectiveness of the program. PE lesson plays a major role in this.